2018
DOI: 10.1037/xlm0000455
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the self-ownership effect: Separating stimulus and response biases.

Abstract: Although ownership is acknowledged to exert a potent influence on various aspects of information processing, the origin of these effects remains largely unknown. Based on the demonstration that self-relevance facilitates perceptual judgments (i.e., the self-prioritization effect), here we explored the possibility that ownership enhances object categorization. The results of 2 experiments supported this prediction. Compared with items owned by a stranger (Expt. 1) or best friend (Expt. 2), those owned by the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
130
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(147 citation statements)
references
References 120 publications
13
130
2
2
Order By: Relevance
“…Model comparisons showed that the best fitting model required the three-parameter model (see Supplementary Materials), consistent with the findings in prior research (Golubickis, Falben, Cunningham, & Macrae, 2018;Golubickis et al, 2017). We then extracted the parameters for each condition and tested the hypothesis by analyzing the posterior probability density of the parameters across the conditions.…”
Section: Diffusion Modellingsupporting
confidence: 77%
“…Model comparisons showed that the best fitting model required the three-parameter model (see Supplementary Materials), consistent with the findings in prior research (Golubickis, Falben, Cunningham, & Macrae, 2018;Golubickis et al, 2017). We then extracted the parameters for each condition and tested the hypothesis by analyzing the posterior probability density of the parameters across the conditions.…”
Section: Diffusion Modellingsupporting
confidence: 77%
“…Previously, Golubickis et al (2018) have demonstrated the benefits of self-relevance (i.e., ownership) on object categorization. In a modified ownership task, participants were initially informed that a class of items (from 2 possible categories) belonged either to the self or another person (i.e., Expt.…”
Section: The Current Researchmentioning
confidence: 99%
“…To explore the processes underpinning task performance, computational modeling (i.e., drift diffusion model (DDM) analysis) will be used to explicate the specific pathway (or pathways) through which ownership influences decisionmaking (e.g., Golubickis et al 2017Golubickis et al , 2018Macrae et al 2017). In any task context, there are two distinct ways in which decisional processing can be biased.…”
Section: The Current Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, ownership paradigms differ in several important respects from the shape-label matching tasks that have dominated work on this topic (Humphreys & Sui, 2016;Sui & Gu, 2017;, but perhaps most significantly in terms of the status of the stimuli on which judgments are rendered (Constable et al, 2019;Falbén et al, 2019;Golubickis, Falbén, Cunningham, & Macrae, 2018;Sui et al, 2012Sui et al, , 2013Sui et al, , 2014Truong, Roberts, & Todd, 2017). Whereas in perceptual-matching tasks geometric shapes serve as proxies for various social targets (e.g., self is a triangle, friend is a square); in ownership tasks, in contrast, everyday objects are linked with the self and others through association (e.g., self owns pens, friend owns pencils).…”
mentioning
confidence: 99%